Technology and Islamic Perspective: A Study of Ethnomathematics - Hasbi, Muhammad; Sarda, Muh; Syafaruddin, Baso (Jurnal Riset dan Inovasi Pembelajaran, 2025)
In the past decade, ethnomathematics-based technology has been prevalent in mathematics teaching, yet Islamic viewpoints are missing. Thus, this systematic analysis explores Islamic and digital culture-based media integration into mathematics education. PRISMA standards were used to collect research that met inclusion criteria for this systematic review. Google Scholar retrieved 2015–2025 research articles. The screening found 40 relevant articles. Thematic analysis categorized 40 papers' research trends and data. From 2020 to 2025, the number of publications increased significantly, peaking in 2024, indicating a greater focus on enhancing mathematics instruction through digital culture media and Islam. The period from 2015 to 2019 indicates a need for further research. Geometry is the main subject, with a few numbers, suggesting growth. Most participants are high school and elementary school kids, highlighting the value of digital culture and Islamic integration at both levels. Questionnaires and performance assessments revealed digital resource usability and Islamic value integration. This review suggests incorporating digital cultural elements and Islamic integration into math education. Using innovative pedagogical methods, technologies, and Islamic principles, educators can create engaging, culturally relevant learning experiences that improve students' arithmetic understanding and appreciation. Additionally, mathematics lessons can solve all problems in Islam by connecting the Quran's Words of God with mathematical concepts. The research is expected to facilitate mathematics learning and show its connection with the Quran. Mathematics lessons will be viewed within religion, not just as a regular subject.